KOMUNITAS CACING TANAH PADA BEBERAPA PENGGUNAAN LAHAN GAMBUT DI KALIMANTAN TENGAH (Earthworms Community on Several Land uses of Peat Land in Central Kalimantan) - Maftuah, Eni; Susanti, Maulia Aries (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Peat land has specific character, depends on depth of peat and peat decomposition rale.Earthworms has a role in decomposition,carbon cycle, nutrient redistribution, bioturbation and cycle of nutrient.The aim of the research was to identify the population and diversity of earthworms on peat soil in central Kalimantan and to get species of dominant earthworm in peat land.The research was carried out in several peat land use in Basarang and Kalampangan, Central Kalimantan within dry and rainy season.The collection of earthworms was by using hand sorting method. The result showed that population of earthworms on mulch was higher than the deep peat.Land use influenced population and diversity of earthworm. The population and diversity of earthworms were highest on pineapple (shallow peat soil).The dominant species earthworm in peat land was Iomoscolex corethurus.